THE PSYCHOLOGICAL FOUNDATIONS OF ATHLETE EDUCATION - Muhammadova.M (International Journal of Literature and Language Studies, 2026)
Annotation:This article discusses the proper distribution of psychological effekts of athletic in achieving high sporting skills and negativi and positive effects of neutral psychological inpact.